THE EFFECT OF THE PROJECT BASED LEARNING MODEL ON THE LEARNING OUTCOMES OF CREATIVE PRODUCTS AND ENTREPRENEURSHIP - Rahayu, Sri; Ahman, Eeng; Nofriansyah, Nofriansyah; Supriatna, Endang; Soffiatun, Soffi (Universitas Indraprasta PGRI, 2025)
This study was conducted to analyze the differences in learning outcomes of Creative Products and Entrepreneurship subjects in grade XI students of SMK Sasmita Jaya 1 before and after the implementation of the Project Based Learning learning model. The method used is Quasi Experiment with Time Series Design design, where only pretest and posttest (final test) are carried out. The research population includes all students of grade XI (XI 1, XI 2, XI 3, and XI 4) totaling 144 people, with a limited sample of one class, namely class XI 3 which consists of 35 students. This research uses data collection techniques through observation, question items, and documentation. Data analysis was carried out by applying a prerequisite test in the form of a normality test, followed by a hypothesis test using a one-sample t-test and a paired sample t-test. In addition, to ensure the validity of the research instrument, tests were carried out on the validity, reliability, differentiation, difficulty, and analysis of the question items as a whole. Based on data analysis, the pretest results of grade XI 3 students of 69.91 experienced a significant increase to 85.54 in the posttest after the implementation of the Project Based Learning model, showing the effectiveness of the model.